SYSTEM OF THE FACTORS INFLUENCING LABOR PRODUCTIVITY IN IT FIRMS - Levon M. Seropov (Статистика и экономика)
Internal and external factors, which inﬂuence labor productivity in IT companies, are considered. Internal factors are considered as fundamental factors, directlyinﬂuencing labor productivity. The analysismethod PESTL is adapted for ﬁ nding out of external factors of labor productivity.